1996
DOI: 10.1007/bf03349840
|View full text |Cite
|
Sign up to set email alerts
|

Effects of melatonin in vivo upon luteinizing hormone and prolactin releases induced by opiate receptor antagonists in adult male rats

Abstract: The effects of melatonin on LH and PRL releases induced by treatment with naloxone, naloxone methyliodide and nalmefene were studied in adult male rats. Subcutaneous melatonin injection (1.4 mg/Kg) had no effect on LH secretion, but caused an inhibition effect (84%) on LH release induced by naloxone (2.4 mg/Kg). Melatonin too totally inhibited LH secretion induced by naloxone methyliodide (2.8 mg/Kg) and nalmefene (2 mg/Kg) when it was simultaneously administered with each opioid receptor antagonist. Melatonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…It is known that the hypothalamic-pituitary axis and the pineal gland play important regulatory roles in the function of gonads (4). ELF magnetic fields are known to influence gonadal function via these indirect mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the hypothalamic-pituitary axis and the pineal gland play important regulatory roles in the function of gonads (4). ELF magnetic fields are known to influence gonadal function via these indirect mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in chickens have shown that melatonin functions as an antioxidant to improve the glutathione peroxidase activity and enhance immunity (Pablos et al 1995). The melatonin can reduce the weight of the gonad and its accessory organs, so it can delay the sexual maturity of the immaturity animals (Shacoori et al 1996). Ayre et al (1992) pointed out that the melatonin binding site in the chicken ovary is located in the follicular cell layer.…”
mentioning
confidence: 99%